Dynamics of Repeated Interviews with Children. Issue 5 (10th June 2016) - Waterhouse, Genevieve F.; Ridley, Anne M.; Bull, Ray; La Rooy, David; Wilcock, Rachel
Summary: Concerns regarding repeat interviews with child witnesses include greater use of suggestive questions in later interviews due to bias, and that children may appear inconsistent and, therefore, be judged as less reliable in court. UK transcripts of first and second interviews with 21 child victims/witnesses (conducted by qualified interviewers) were coded for question types and child responses. Interviewers were consistent in their proportional use of question types across interviews. Furthermore, children were as informative in second interviews as in first, mostly providing new details consistent with their prior recall. Despite the apparent lack of training in conducting repeated interviews, no negative effects were found; second interviews appeared to be conducted as well as initial interviews, and children provided new details without many contradictions. It is suggested that when a child's testimony is paramount for an investigation, a well‐conducted supplementary interview may be an effective way of gaining further investigative leads.Copyright © 2016 John Wiley & Sons, Ltd.